Utilization of waste for the generation of value-added products - Mohd. Salleh, Hamzah (IIUM Press, 2022)
Utilization of renewable biomass waste for the production of value-added products is one of the pertinent sustainable strategies. There are various waste materials abundantly available which are harmful if discharged to the environment untreated. The backlash of waste generation from settlements and industries poses serious waste management problem causing health hazards and degradation of the environmental quality. This prompted biotechnologists, engineers and scientists to engage in materials and biotechnology research aiming at turning waste to wealth. For that to be realized conversion process became quite pertinent. Progress in this area was augmented in the localities which did not have enough lands for waste disposal. This way, waste utilization became the integral part of waste reduction and waste management strategies. The utilization of waste helps alleviate degradation of the quality of the environment. This became popular in developing and least developed countries because waste to wealth efforts has high potential of income generation. The best example is producing biodiesel from empty fruit bunches and ethanol manufacturing from sugar industry wastes. The purpose of bringing out this volume is to present a conglomeration of articles comprising a variety of researches related to conversion of waste into value added products and some treatment methods. As no book on biochemical research can cover all its areas, this concise book will discuss some of the pertinent aspects of this branch of science and engineering. The authors would like to acknowledge the contributions of Dr. Amal A. Elgharbawy, Nik Rashida Nik Abdul Ghani and Mohd Nazri Mohd Nawi during the preparation of the book.